2018
DOI: 10.3390/en11020339
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Reservoir Stimulation on Marine Gas Hydrate Conversion Efficiency in Different Accumulation Conditions

Abstract: Abstract:In this paper, we used a method of combining reservoir stimulation technique (RST) with depressurization to investigate the conversion efficiency of marine natural gas hydrate (NGH) reservoirs in the Shenhu area, on the northern slope of the South China Sea, which differ in intrinsic permeability and initial NGH saturation conditions. We also analyzed the influence of the variable-stimulation effect on marine NGH conversion efficiency in different accumulation conditions, providing a reference scheme … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 32 publications
(42 reference statements)
0
11
0
Order By: Relevance
“…Yang et al investigated the influence of different strategies of hydraulic fracturing on the conversion efficiency of gas hydrate under different saturation and intrinsic permeability and attempted to optimize the operation. 144 It was denoted that hydraulic fracturing substantially increased the gas hydrate conversion efficiency and the density of fractured networks had great influence for the conversion efficiency. In addition, under lower permeability and saturation conditions, the improvement effect of hydraulic fracturing became more obvious, which indicated that it was more preferable for the hydrate exploitation in the SCS.…”
Section: Advances On Natural Gas Hydratementioning
confidence: 99%
See 1 more Smart Citation
“…Yang et al investigated the influence of different strategies of hydraulic fracturing on the conversion efficiency of gas hydrate under different saturation and intrinsic permeability and attempted to optimize the operation. 144 It was denoted that hydraulic fracturing substantially increased the gas hydrate conversion efficiency and the density of fractured networks had great influence for the conversion efficiency. In addition, under lower permeability and saturation conditions, the improvement effect of hydraulic fracturing became more obvious, which indicated that it was more preferable for the hydrate exploitation in the SCS.…”
Section: Advances On Natural Gas Hydratementioning
confidence: 99%
“…So far, the most accessible reservoirs stimulation technique for gas hydrate reservoirs is hydraulic fracturing. Yang et al investigated the influence of different strategies of hydraulic fracturing on the conversion efficiency of gas hydrate under different saturation and intrinsic permeability and attempted to optimize the operation . It was denoted that hydraulic fracturing substantially increased the gas hydrate conversion efficiency and the density of fractured networks had great influence for the conversion efficiency.…”
Section: Advances On Natural Gas Hydrate Exploitation In the Scsmentioning
confidence: 99%
“…The interaction between the factors shall not be underestimated [50]. Due to the limitation of the single factor experiments, the continuous point cannot be analyzed, and the interaction among various factors is not considered.…”
Section: Response Surface Analysis Of Variables To Srvmentioning
confidence: 99%
“…The most typical hydrate-forming gas is methane, and NGH mainly occurs in terrestrial permafrost and offshore sediments where low temperature and high-pressure conditions needed by hydrate stabilization are met (Collett, 2002;Koh, 2002;Chong et al, 2016). As a potential new unconventional energy, NGHs are currently attracting significant attention owing to their extensive distribution, great resource potential, high energy density, and low environmental pollution (Koh et al, 2012;Yang et al, 2018). Current estimations of the hydrate-containing hydrocarbon gas available at standard conditions ranges from 10 15 to 10 18 m 3 , which is twice as much as the conventional fossil energy (Moridis et al, 2009a).…”
Section: Introductionmentioning
confidence: 99%